Development of Innovative Mediterranean-Style Semi-Hard Goat’s Cheese Supplemented with Seaweeds (Palmaria palmata and Ulva sp.) and Its Characterization - Bruno M. Campos; Bruno S. Moreira-Leite; Abigail Salgado; Edgar Ramalho; Isa Marmelo; Manuel Malfeito-Ferreira; Paulo H. M. de Sousa; Adolfo Henriques; João P. Noronha; Mário S. Diniz; Paulina Mata (Applied Sciences)
The main objective of this study was the development of two semi-hard goat cheeses supplemented with Palmaria palmata and Ulva sp. with the aim of developing innovative food products, increasing the concentration of nutrients in these cheeses and familiarizing consumers with seaweed-containing foods. The impact of seaweed addition was evaluated through physicochemical, microbiological, and organoleptic properties of the semi-hard goat cheeses. Carbohydrate content was relatively low, whereas the total lipid content was relatively high (particularly in semi-hard goat cheese supplemented with seaweeds). Crude protein content presented higher values in semi-hard goat cheese supplemented with Ulva sp. The semi-hard goat cheese supplemented with Ulva sp. shows increased levels of Ca, Fe, Mn, and Zn. Instrumental color and the textural parameters of semi-hard goat’s cheese varied significantly with seaweed addition. Most of the microbiological load complies with the Portuguese (INSA) and the United Kingdom’s (HPA) guidelines for assessing the microbiological safety of ready-to-eat foods placed on the market. Additionally, the Flash Profile scores of semi-hard goat cheeses supplemented with seaweeds highlighted aroma and flavor complexity. Overall, this study confirms the potential of using seaweeds as a viable alternative to produce semi-hard goat cheeses with less pungency or goat milk flavor, making this product more pleasant and appealing to consumers sensitive to these sensory characteristics.